2003
DOI: 10.1128/aem.69.7.3919-3923.2003
|View full text |Cite
|
Sign up to set email alerts
|

Group A Rotavirus in Sewage Samples from Barcelona and Cairo: Emergence of Unusual Genotypes

Abstract: The presence of rotavirus strains in sewage samples from Cairo, Egypt (November 1998 to October 1999), and Barcelona, Spain (November 1998 to December 2002), was investigated by using a generic molecular detection method based on amplification of a VP6 gene fragment. Overall, 85.7 and 66.9% of the sewage samples from Cairo and Barcelona, respectively, were positive. Positive samples were characterized further, and VP7 and VP4 genotypes were determined. Although 30% of the positive samples from Cairo were G unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
96
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 31 publications
16
96
1
2
Order By: Relevance
“…Villena et al [33] found that rotaviruses were detected in 85.7% of raw sewage samples in wastewater treatment plants in Cairo. The variation in rotavirus percentage of frequency may be due to increasing of population in Cairo than the population in El-Mofti village.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Villena et al [33] found that rotaviruses were detected in 85.7% of raw sewage samples in wastewater treatment plants in Cairo. The variation in rotavirus percentage of frequency may be due to increasing of population in Cairo than the population in El-Mofti village.…”
Section: Discussionmentioning
confidence: 99%
“…The primers VP6-3 5-GCTTTAAAACGAAGTCTTCAAC-3 and VP6-4 5-GGTAAATTACCAATTCCTCCAG-3 were used for amplification of a fragment of the VP6-coding gene corresponding to nucleotides 2-187 for rotavirus with a predicted product size of 190 bp [33] .…”
Section: Rotavirus Detection Using Rt-pcrmentioning
confidence: 99%
“…In Spain, G5 rotavirus strains have not been detected in human clinical samples. Locally, in Barcelona, Villena et al (45) detected only three G5 strains (2%) in 104 sewage samples. One of these samples was associated with a P [8] type, while the other two could not be associated with any P type but were closely related to porcine strains by phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangkok, 25% of the sewage samples were positive for rotavirus using RT-nested PCR (Kittigul et al 2005). A RT-PCR hybridization was used in a study from Barcelona and Cairo, where 66.9% and 85.7% of sewage samples were positive for rotavirus, respectively (Villena et al 2003). A study in France reported a prevalence of rotavirus in raw sewage of 42% (Dubois et al 1997).…”
Section: Discussionmentioning
confidence: 99%